Corporate financial policy and the value of cash under uncertainty. Issue 2 (3rd April 2017) - Chakraborty, Atreya; Baum, Christopher F.; Liu, Boyan
Abstract : Purpose: The purpose of this paper is to provide evidence on how firm-specific and macroeconomic uncertainty affects shareholders' valuation of a firm's cash holdings. This extends previous work on this issue by highlighting the importance of the source of uncertainty. The findings indicate that increases in firm-specific risk generally increase the value of cash while increases in macroeconomic risk generally decrease the value of cash. These findings are robust to alternative definitions of the unexpected change in cash. The authors extend the analysis to financially constrained and unconstrained firms. Design/methodology/approach: The authors test the hypothesis that the marginal effect of cash holdings on excess stock returns is sensitive to uncertainty. To compute this marginal effect, the authors adopt and extend the approach of Faulkender and Wang (2006) to the authors' more elaborate model. Findings: The findings indicate that different sources of uncertainty affect the value of cash holdings differently. Findings indicate that increases in firm-specific risk generally increase the value of cash while increases in macroeconomic risk generally decrease the value of cash. These findings are robust to alternative definitions of the unexpected change in cash. The authors also extend the findings to financially constrained and unconstrained firms. Originality/value: The findings indicate that the source of uncertainty firm-specific vs macroeconomic risk matters. The two sources of risk may have quite different effects on shareholders' valuation of a firm's cash holdings. Results from alternative sources of findings are new. These new findings are robust to alternative definitions of the unexpected change in cash.